FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TB PARU PADA ANAK (STUDI DI SELURUH PUSKESMAS DI KABUPATEN MAGELANG) - Rusliana Apriliasari; Retno Hestiningsih; Martini Martini; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Tuberculosis is a disease caused by the entry of Mycobacterium tuberculosis into the body through the respiratory cavity. Based on the Health Profile of Magelang District, there was a significant increase of cases of pulmonary tuberculosis in children. In 2014 there were no cases of pulmonary TB in children, while in 2015 found 81 (11%) cases of pulmonary TB in children. This study aims to analyze related factors to the incidence of children tuberculosis in Magelang District from January 2016-June 2017. This study was conducted using observational analytic method with case control study. The sample used in this study were 100 respondents, consisting of 50 cases and 50 controls.. The results of statistical tests showed that there were several factors related to pulmonary TB incidence in children. There are contact history (p=0,018; OR=3,143; 95% CI=1,291–7,653), floor type (p=0,031; OR=2,897, 95% CI=1,187–7,067), ventilation area (p=0,004; OR=3,717; 95% CI=1,581–8,738), lighting level (p=0,024; OR=3,218; 95% CI=1,248–8,299), humidity (p=0,009; OR=3,160; 95% CI=1,397–7,152), parent income level (p=0,009; OR=3,188; 95% CI=1,403–7,241), parent education level (p=0,009; OR=3,579; 95% CI=1,437–8,913), and parents knowledge level (p=0,02; OR=3,020; 95% CI=1,265–7,209). It is suggested to Magelang Regency Health Office to improve health promotion related to healthy house requirement and improvement of clean and healthy life behavior to avoid transmission of tuberculosis disease.